2018
DOI: 10.4172/2572-0775.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Humor and Laughing: The Benefit of Hospital Clowns in Pediatrics for Hospitalized Children and their Families: A Review

Abstract: Introduction: Laughter and humor have been reported as an effective way to achieve physiological and psychological health-related benefits to reduce pain and increase stress tolerance during medical evaluation and painful procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(216 reference statements)
0
1
0
Order By: Relevance
“…Studies so far mainly looked at the effect of clown visits on children who had to undergo surgery or invasive procedures and their parents. In recent reviews, it was concluded that medical clowns help in reducing psychological distress, anxiety and pain in these children and their parents (Phal, Tardieu, ALessandrini, Gentile, & Rindstedt, 2018; Sridharan & Sivaramakrishnan, 2016; Zhang, Yang, Lay, Garg, & Lao, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Studies so far mainly looked at the effect of clown visits on children who had to undergo surgery or invasive procedures and their parents. In recent reviews, it was concluded that medical clowns help in reducing psychological distress, anxiety and pain in these children and their parents (Phal, Tardieu, ALessandrini, Gentile, & Rindstedt, 2018; Sridharan & Sivaramakrishnan, 2016; Zhang, Yang, Lay, Garg, & Lao, 2017). …”
Section: Introductionmentioning
confidence: 99%